The Development of Innovative Science Learning Tools to Develop 21st Century Skills for Elementary School Teachers Naskat II Santo Ignatius Olilit Timur - Leasa, Marleny; Batlolona, John Rafafy (Unram Journal of Community Service, 2024)
The Tanimbar Islands are one of the areas in Maluku Province which is classified as an underdeveloped area in Indonesia and is included in the 3T category. This district borders directly with Australia. The underdevelopment of the Tanimbar Islands covers various sectors including education. The quality of teachers, availability of books, and other facilities and infrastructure are still very minimal. The results of observations and discussions with teachers at Naskat II Elementary School Santo Ignatius Olilit Timur showed that the development of devices is still less innovative because teachers do not participate in training that supports improving teacher competence in science learning in the classroom. Therefore, the purpose of this service is to increase the capacity of teachers in developing innovative learning devices to support 21st century life skills. Therefore, professional lecturers from the Faculty of Teacher Training and Education, Pattimura University, conducted training and mentoringin developing learning tools based on innovative learning.The results achieved from this activity mentoring are 86.28%teachers have been able to develop science learning tools well. Therefore, it is important for lecturers, Widyaiswara at the Education Quality Assurance Center (BPMP) in each province, school supervisors and education observers to continue to collaborate with teachers in sharing experiences and knowledge in improving teacher capacity